Imaging Acute Stroke: From One-Size-Fit-All to Biomarkers - Lu, Jianfei; Mei, Qiyong; Hou, Xianhua; Manaenko, Anatol; Zhou, Lili; Liebeskind, David S.; Zhang, John H.; Li, Yao; Hu, Qin (Frontiers in Neurology, 2021)
In acute stroke management, time window has been rigidly used as a guide for decades and the reperfusion treatment is only available in the first few limited hours. Recently, imaging-based selection of patients has successfully expanded the treatment window out to 16 and even 24 hours in the DEFUSE 3 and DAWN trials, respectively. Recent guidelines recommend the use of imaging techniques to guide therapeutic decision-making and expanded eligibility in acute ischemic stroke. A tissue window is proposed to replace the time window and serve as the surrogate marker for potentially salvageable tissue. This article reviews the evolution of time window, addresses the advantage of a tissue window in precision medicine for ischemic stroke, and discusses both the established and emerging techniques of neuroimaging and their roles in defining a tissue window. We also emphasize the metabolic imaging and molecule imaging of brain pathophysiology, and highlight its potential in patient selection and treatment response prediction in ischemic stroke.